Impact of electron irradiation upon optical properties of Bismuth/Yttria codoped phosphosilicate fiber. (August 2020) - Kir'yanov, A.V.; Halder, A.; Sekiya, E.; Saito, K.; Barmenkov, Y.O.; Minkovich, V.P.; Didenko, S.I.; Legotin, S.A.; Tapero, K.I.
Highlights: Changes in Bi-doped fiber properties after irradiation by electron beam are studied. Waveguide properties of Bi-doped fiber in pristine and irradiated states are modeled. Ways to use Bi-doped fiber for dosimetry in harsh environments are proposed. Stokes shift of cutoff wavelength vs . exposure dose is discovered for Bi-doped fiber. Abstract: We report the changes in absorption and emission properties of Bismuth/Yttria codoped phosphosilicate fiber which arise after bombardment by a beam of high-energy (β) electrons. Despite dramatic rise of induced absorption in the fiber as the result of β-irradiation, reaching 2000 dB/m in the visible, we reveal its remarkable resistance, at doses of exposure up to 10 14 cm −2, in terms of the emissive potential in the visible / near-IR and photo-bleaching contrast at pump wavelengths falling into the absorption bands of Bismuth active centers. Also, we uncover a novel effect of large spectral shift to the Stokes side (up to 75 nm), experienced by the cutoff wavelength of the fiber in function of β-irradiation dose due to notable refractive index rise in its core region.